2020
DOI: 10.1002/jsfa.10478
|View full text |Cite
|
Sign up to set email alerts
|

Functional compounds from olive pomace to obtain high‐added value foods – a review

Abstract: Olive pomace, the solid by‐product from virgin olive oil extraction, constitutes a remarkable source of functional compounds and has been exploited by several authors to formulate high value‐added foods and, consequently, to foster the sustainability of the olive‐oil chain. In this framework, the aim of the present review was to summarize the results on the application of functional compounds from olive pomace in food products. Phenolic‐rich extracts from olive pomace were added to vegetable oils, fish burgers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 118 publications
(132 reference statements)
2
47
0
Order By: Relevance
“…In recent years, the massive use of plastic materials has inevitably led to an increase in issues related to environmental pollution and the disposal of these materials [91]. To tackle this problem, interest in sustainable packaging made with biopolymers from renewable agro-industrial sources, widely available and cheap, is growing [92][93][94]. In Table 2 are reported the possible applications of vine and winery by-products as fillers for food packaging.…”
Section: Food Packaging Formulationsmentioning
confidence: 99%
“…In recent years, the massive use of plastic materials has inevitably led to an increase in issues related to environmental pollution and the disposal of these materials [91]. To tackle this problem, interest in sustainable packaging made with biopolymers from renewable agro-industrial sources, widely available and cheap, is growing [92][93][94]. In Table 2 are reported the possible applications of vine and winery by-products as fillers for food packaging.…”
Section: Food Packaging Formulationsmentioning
confidence: 99%
“…It is in those areas that efforts should be made to improve the knowledge about the advantages of the use of MD approaches. For example, recovery of bioactives from foods or food by-products has become an hot topic in recent years [31][32][33] but, despite this interest, in our research only few works have been found that optimize the extraction mixtures according to MD.…”
Section: Resultsmentioning
confidence: 95%
“…It was shown that tea drugs and plant extracts high in polyphenols such as black tea, green tea, Grape seed extract, Grapefruit seed extract, Origanum and leaves of the Ribes nigrum increase the erosion protective properties of the pellicle [178,183]. Further, typical pellicle components like histatines and PrPs interact with polyphenols, building complexes in saliva and pellicle [185,186]. This is the reason for the astringent character of polyphenols [186].…”
Section: Mechanisms For Provided Effects By Polyphenols 81 Effect Of Polyphenols On Oral Proteinsmentioning
confidence: 99%
“…Typical salivary proteins for polyphenol-protein interactions are histatins and prolin rich proteins (PrPs). They also represent typical pellicle proteins [ 151 , 185 , 186 , 187 ]. It was shown in a recent proteome analysis that ECGC can increase the abundance of important pellicle proteins e.g., prolin rich proteins (PRPs), calcium-bind proteins and statherin [ 188 ].…”
Section: Pellicle Formation and Initial Bacterial Colonization On Solid Surfacesmentioning
confidence: 99%
See 1 more Smart Citation